2014
DOI: 10.1080/15222055.2014.920750
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect on Embryo Mortality and Fry Growth from Adult Coho Salmon Subjected to Electronarcosis Prior to Spawning

Abstract: The use of electronarcosis as a fish immobilization technique has reemerged in recent years. Previous studies have investigated behavioral effects of the technique. But investigations of the physical and physiological effects on fish of electrical immobilization have focused on different electrical waveforms or higher power densities than are used for electronarcosis. This study was designed to determine whether there was a significant negative effect on embryo survival or fry growth among the progeny of adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Kynard and Lonsdale (1975) and Curry and Kynard (1978) applied EN to salmonids for up to 6 h without mortality. There was no effect on embryo survival or fry growth among the progeny of adult Coho Salmon that were immobilized with EN (Hudson et al 2014). Study fish under EN were generally calm and easy to handle.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Kynard and Lonsdale (1975) and Curry and Kynard (1978) applied EN to salmonids for up to 6 h without mortality. There was no effect on embryo survival or fry growth among the progeny of adult Coho Salmon that were immobilized with EN (Hudson et al 2014). Study fish under EN were generally calm and easy to handle.…”
Section: Discussionmentioning
confidence: 96%
“…Voltage gradient was measured as the voltage applied to electrodes divided by the distance between electrodes. Multiple researchers have reported success in achieving EN at voltage gradients between 0.25 and 0.56 V/cm (Kynard and Lonsdale 1975;Curry and Kynard 1978;Hudson et al 2014). Conductivity of treatment water was not measured during tagging but typically ranges between 50 and 100 mS/cm in the Klickitat River (Yakama Nation Fisheries, unpublished data).…”
mentioning
confidence: 99%
“…Hudson et al. () observed that survival of embryos produced from adult Coho Salmon O. kisutch treated with EN was similar to that of embryos from MS‐222‐treated adults. In these studies, EN was considered preferable to CO 2 or MS‐222 due to faster induction and recovery times.…”
mentioning
confidence: 98%
“…Most recently, however, electrical immobilization (i.e., electroimmobilization) of fish has gained more interest as an alternative method (Hudson et al. ; Rous et al. ; Kim et al.…”
mentioning
confidence: 99%
“…Commonly used methods for immobilizing fish include immersion of fish into chilled or CO 2 -saturated water, as well as application of chemicals such as tricaine methanesulfonate or eugenol (clove oil) to the water (Fish 1942;Anderson et al 1997;Pirhonen and Schreck 2003). Most recently, however, electrical immobilization (i.e., electroimmobilization) of fish has gained more interest as an alternative method (Hudson et al 2015;Rous et al 2015;Kim et al 2017).…”
mentioning
confidence: 99%